Water quantity and quality in the Zerafshan River Basin: only an upstream riparian problem? - Olsson, O.; Wegerich, Kai; Kabilov, F. (Informa UK Limited, 2012)
In discussing the 1997 UN Watercourse Convention, McCaffrey (1998) gave a theoretical example of the late-developer problem. This paper complements that theoretical example with a real case study of the Zerafshan basin in Central Asia. While McCalliey addressed the water quantity issue in his example, the focus here also includes water pollution. The aim of the paper is to analyze some of the provisions of the mechanisms in the field of international water law- the Helsinki Rules and the UN Watercourses Convention- for water quantity and quality aspects, as well as to provide an insight into the basin regarding these two aspects.